O exercício abusivo do poder econômico nas relações de trabalho - Deo, Julia de Biase (2023)
This paper´s aim is to investigate a concept that is not new, but which has only gained greater relevance and prominence in recent years: the abuse of monopsony power in labor relations. The idea of monopsony, created as an opposition to the concept of monopoly, is not always remembered by the antitrust authorities, that usually focus their analysis on abuses performed by suppliers; those that take place from the seller's perspective. However, as this research will reveal, in some scenarios, buyers and demanders can also have sufficient economic power to unbalance perfect competition. Faced with this issue, this study will focus on the anticompetitive practices that monopsonist and olipsonist agents can engage in, especially in the labor market. In this context, this study will mainly focus on conducts that have been the main point of attention by the authorities, i.e.: no-poach agreements, wage-fixing agreements, and the exchange of competitively sensitive information regarding compensation and other employment conditions. With the new soft law documents published in recent years and recent precedents, the topic to be explored is of obvious importance and contemporaneity